A Carnal Map-Aware Chord Model Created on ANT Colony Optimization - Thamaraiselvan, N; Immaculate Mercy, A (International Journal of Computer Sciences and Engineering, 2025)
On the basis of in-depth analysis of the mapping storage methods of the Identifier-Locator separation network, this paper proposed a physical topology awarded Chord model (Ant-Chord) which based on ant colony algorithm. The ideas of Ant-Chord is to regard the storage nodes in the whole Chord as a TSP problem and solve the TSP problem quickly by using the ant colony algorithm, then to build the Chord with the obtained TSP solution, and proposed a method which called "Luoyang shovel" to optimize the Ant-Chord’s routing hops. The model is simple and easy to implement, which has small changes within the original Chord model and little extra overhead cost in the routing table storage. Simulation results show that, AntChord has obvious advantages in average routing hops and delay in comparison with other Chord model.